T lymphocyte dynamics in methylisothiazolinone‐allergic patients. (3rd May 2016) - Popple, Amy; Williams, Jason; Maxwell, Gavin; Gellatly, Nichola; Dearman, Rebecca J.; Kimber, Ian
Summary: Background: Methylisothiazolinone (MI), a preservative that is commonly used in personal care products, is now recognized as an important contact allergen in both cosmetic and occupational settings. Objectives: To analyse T lymphocyte responses to MI, in order to provide important information regarding the relationship between the nature of such responses and skin sensitization potency. Methods: Proliferative responses to free MI and to an MI–human serum albumin (HSA) conjugate were measured according to [ 3 H]thymidine incorporation (n = 56 donors; patch test scores of + in 20, ++ in 29, and +++ in 7). Peripheral blood mononuclear cells were cultured in the presence of MI (0.001–1 µg/ml) or MI–HSA (0.001–100 µg/ml). Proliferating CD4 + and CD8 + T lymphocytes were identified by flow cytometry with the intracellular marker Ki‐67. Results: For free MI, modest positive responses were recorded for 7 of 31 donors. In contrast, MI–HSA stimulated more marked responses in 17 of 31 donors. Characterization of positive proliferative responses showed variable patterns of proliferating CD4 + and CD8 + T lymphocytes from donors with the same patch test scores and similar maximal values. Conclusions: MI–HSA is able to induce secondary responses in lymphocytes drawn from sensitized subjects, and provides a more effective source of antigen than free MI. Furthermore, individual donors show differential activity profiles with respect to T lymphocyte subsets.